Expression of tumor growth related genes in IRE1 knockdown U87 glioma cells: effect of hypoxia - O. H. Minchenko; O. Y. Luzina; O. S. Hnatiuk; D. O. Minchenko; I. A. Garmash; O. O. Ratushna (The Ukrainian Biochemical Journal, 2017)
We have studied the effect of IRE1 signaling enzyme knockdown as well as hypoxia on the expression of genes encoding the important tumor growth related proteins (BRCA1, DEK, BCL2L1, COL6A1, TPD52, HOMER3, and GNPDA1) in U87 glioma cells. It was shown that the expression level of breast cancer 1 early onset (BRCA1) and tumor protein D52 (TPD52) mRNAs are strongly up-regulated in U87 glioma cells by down-regulation of IRE1 expression in comparison with the control cells. At the same time the expression level of collagen, type VI, alpha 1 (COL6A1), DEK oncogene (DEK), glucosamine-6-phosphate deaminase 1 (GNPDA1) and homer homolog 3 (HOMER3) was significantly down-regulated in glioma cells under these experimental conditions. It was also shown that hypoxia up-regulated the expression level of COL6A1 and TPD52 mRNAs and down-regulated – BRCA1, DEK, and GNPDA1 mRNAs in control glioma cells and that down-regulation of IRE1, which control cell proliferation and tumor growth, modified the effect of hypoxia on the expression of COL6A1, DEK, BCL2L1, HOMER3, and GNPDA1 genes. The present study demonstrated that hypoxia affected the expression of most studied genes in IRE1-dependent manner.